Surface Treatment and Bioinspired Coating for 3D-Printed Implants - Liu, Junyi; Mohd Rafiq, Nafisah Bte; Wong, Lai Mun; Wang, Shijie (Frontiers in Chemistry, 2021)
Three-dimensional (3D) printing technology has developed rapidly and demonstrates great potential in biomedical applications. Although 3D printing techniques have good control over the macrostructure of metallic implants, the surface properties have superior control over the tissue response. By focusing on the types of surface treatments, the osseointegration activity of the bone–implant interface is enhanced. Therefore, this review paper aims to discuss the surface functionalities of metallic implants regarding their physical structure, chemical composition, and biological reaction through surface treatment and bioactive coating. The perspective on the current challenges and future directions for development of surface treatment on 3D-printed implants is also presented.